Analisis Kompetensi Kepribadian Guru Sekolah Menengah Pertama dalam Meningkatkan Etika Profesionalisme Mengajar - Meza Aulia Zahrah; Rasti Ananda; Ristia Rahmadani; Ade Irma (Lembaga Pengembangan Kinerja Dosen, 2025)
Teacher personality is very important in shaping student character and creating a positive learning environment at school. This element not only demonstrates the values of integrity and good attitude but also forms the foundation for building relationships between teachers and students, among fellow teachers, and with all school members. This article aims to explain the personality competencies of teachers based on interviews conducted in three schools with different contexts. This research uses a descriptive qualitative approach, with data collection methods through in-depth interviews involving teachers and principals. The results obtained show that teachers generally demonstrate discipline, responsibility, and exemplary behavior. However, there are still some challenges such as heavy workloads and a lack of further training. These findings emphasize the importance of continuous teacher character development and systematic support to maintain the quality of education.